Розвиток посівної техніки в Україні в кінці ХІХ – на початку ХХ ст. - Лупаренко, Г.В. (Питання історії науки і техніки, 2008)
В статье рассматривается конструкция основных типов посевных орудий и машин ХІХ века, распространённых на территории современной Украины. Кратко описаны основные технические усовершенствования конструкции посевных машин, осуществленные и внедренные на отечественных предприятиях. In this article the construction of the main types of the XIX centuries sown machines, which were spread on the territory of modern Ukraine, are considered. The main technical improvements of the construction of the sown machines had been described which were later realized and established on the native plants.